Agents that inhibit histamine release: A review - Gomes, J. C. (My University, 1992)
It is well known that histamine is found in high concentration in mast cell granules(1). The histamine content of these granules may be released to the extracellular space if an appropriate stimulus is provided(2). Besides histamine, other preformed active substances like enzymes, chemotatic factors and proteoglycans, as well as newly generated mediators like eicosanoids, platelet activating factor and adenosine are released during the secretion process of mast cells(3). The activation of mast cell degranulation has been associated with a number of pathologic disorders, most frequently, diseases derived from the atopic state(4). It is now evident that mast cells are the primary effector cells in the early reaction in both allergic and non-allergic asthma(5,6), although some authors doubt that the late reaction of asthma is a mast cell dependent event(6). Other studies point towards basophils as cellular elements involved in the secondary phase of inflammation in allergic diseases(7). Secretion would depend on a histamine releasing factor, and on the presence of IgE on the basophil's surface(8). There is also evidence suggesting involvement of mast cells in some non-allergic inflammatory processes like arthritis(9). The pharmacological management of these diseases basically consists in the use of methylxantines, beta 2-adrenergic agonists, glucocorticoids, sodium cromoglycate-like drugs, anticholinergic and antihistaminic H 1 antagonists(10). Their therapeutic effects include bronchodilatation, receptor and physiological antagonism, prevention of inflammatory responses induced by secondary cells, and finally, inhibition of mast cell activation(11). This review is concerned with compounds having inhibitory action on mast cell activation, and their possible importance on the pathophysiology of mast cell-related diseases.
Keywords: adenosine; adrenalin; azatadine; azelastine; calcimycin; calcium channel blocking agent; ceterizine; concanavalin a; cromoglycate disodium; dextran; histamine h1 receptor antagonist; histamine release inhibitor; icosanoid; isoprenaline; ketotifen; nedocromil; phenothiazine derivative; plant extract; proteoglycan; terfenadine; theophylline; thrombocyte activating factor; unclassified drug; animal tissue; antiinflammatory activity; conference paper; histamine release; human; human tissue; mast cell; mast cell degranulation; nonhuman; priority journal; Animal; Histamine Antagonists; Histamine Release; Human